AN ANALYSIS OF GRAMMATICAL ERRORS IN THE 1ST YEAR STUDENTS’ WRITINGS AT ENGLISH DEPARTMENT, ANDALAS UNIVERSITY - Rury Novita (Vivid: Journal of Language and Literature, 2014)
Error analysis is a way to investigate errors in the second or foreign language acquisition.  In this thesis, error analysis is conducted to find the grammatical errors committed by the first year students of English Department at Andalas University in writings. The data were collected from the essays written by the students in Essay Writing class. The research is conducted following the steps proposed by James (1998). They are data collection, error detection, locating error, describing error, and diagnosing error. The theory used is James’ (1998) about the combined taxonomy of errors and the cause of the errors. It is supported by Lado’s theory (1957) about the types of interference. From the analysis of the data, it is found that the most frequent error committed by the students is in verb and tense while the most frequent category of error is misinformation. Furthermore, it is also found that the errors are mostly caused by intralingual factor.Keywords: grammatical error, intralingual, interlingual